Fabrication of electrospun cellulose/chitosan/ball-milled bone char membranes for efficient and selective sorption of Pb(II) from aqueous solutions - Xuan, Du; Abdul Rashid, Suraya; Abdullah, Luqman Chuah; Abdul Rahman, Norizah (Springer Nature, 2023)
Separation materials have received increasing attention given their broad applications in the management of environmental pollution. It is desired to balance the contradiction between high separation efficiency and selectivity of separation materials. The integration of ball-milled bone chars with electrospun membranes might achieve this balance. In this study, electrospun cellulose/chitosan/ball-milled bone char (CL/CS/MB) membranes were by well-dispersing ball-milled bone chars with nanoscale size (98.9–167.5 nm) and developed porosity (40.2–373.1 m2/g) in the electrospinning solvent. The synergistic integration of distributed MBs (5.4–31.5 wt.% of loading hydroxyapatite on the membrane matrix) allowed the efficient sorption of Pb(II) with fast kinetics (20.0 min), excellent capacity (219.9 mg/g at pH 5.0, T 298 K), and favorable selectivity coefficients (2.76–6.79). The formation of minerals was dominant for the selective sorption of Pb(II) by combining the spectral analysis and quantitative determination. The surface complexation with O-/reductive N-species, the cation exchange with inorganic Ca2+, the electrostatic attraction with deprotonated O−, and the cation-π coordination with the aromatic carbon via the π-electrons should be not ignored for the capture of Pb(II). This work demonstrated the feasibility of electrospun CL/CS/MB membranes as a promising candidate for the remediation of aquatic pollutants.